Gene duplication and divergence produce divergent MHC genotypes without disassortative mating. Issue 17 (29th July 2016) - Dearborn, Donald C.; Gager, Andrea B.; McArthur, Andrew G.; Gilmour, Morgan E.; Mandzhukova, Elena; Mauck, Robert A.
Abstract: Genes of the major histocompatibility complex (MHC) exhibit heterozygote advantage in immune defence, which in turn can select for MHC‐disassortative mate choice. However, many species lack this expected pattern of MHC‐disassortative mating. A possible explanation lies in evolutionary processes following gene duplication: if two duplicated MHC genes become functionally diverged from each other, offspring will inherit diverse multilocus genotypes even under random mating. We used locus‐specific primers for high‐throughput sequencing of two expressed MHC Class II B genes in Leach's storm‐petrels, Oceanodroma leucorhoa, and found that exon 2 alleles fall into two gene‐specific monophyletic clades. We tested for disassortative vs. random mating at these two functionally diverged Class II B genes, using multiple metrics and different subsets of exon 2 sequence data. With good statistical power, we consistently found random assortment of mates at MHC. Despite random mating, birds had MHC genotypes with functionally diverged alleles, averaging 13 amino acid differences in pairwise comparisons of exon 2 alleles within individuals. To test whether this high MHC diversity in individuals is driven by evolutionary divergence of the two duplicated genes, we built a phylogenetic permutation model. The model showed that genotypic diversity was strongly impacted by sequence divergence between the most common allele of each gene, with a smaller additional impact of monophyly of the two genes. Divergence of allele sequences between genes may have reduced the benefits of actively seeking MHC‐dissimilar mates, in which case the evolutionary history of duplicated genes is shaping the adaptive landscape of sexual selection.